Gummy candies production with natural sugar source: Effect of molasses types and gelatin ratios - Kurt, Abdullah; Bursa, Kubra; Toker, Omer Said (SAGE PUBLICATIONS LTD, 2022)
Nowadays, attention has been dedicated towards the development of foodstuffs whose constituents are from natural sources. In this study, grape, mulberry, and carob molasses containing natural sugars were evaluated in order to replace the use of sugar syrup and artificial additives in the production of gummy candy which was prepared by varied gelatin ratios. The molasses which have similar degrees Brix values (78-79) presented different types and amounts of sugar components. High invert sugar with low sucrose was observed in grape and mulberry but high sucrose with low fructose and glucose appeared in carob molasses. Unlike grape and mulberry, carob based jellies had a whitish appearance possibly as a result of the crystallization due to its high sucrose/invert sugar ratio. For all parameters of TPA, carob candy with 5 g/100 g gelatin and grape candy with 10 g/100g gelatin had the lowest and highest values, respectively. Gelatin concentration dependency trend of hardness, gumminess, chewiness and resilience was determined as grape > mulberry > carob. No significant effect (p > 0.05) on gelling temperatures (21-29 degrees C) but significant effect (p < 0.05) on melting points (33-39 degrees C) of molasses types were observed for candies. The properties of grape based candy having higher thermal stability and lower temperature sensitivity were attributed to its higher total sugar contents than other samples. The sensorial acceptability score for molasses gummy candies obtained more than 3.0 on a 5-point hedonic scale. These results illustrate the potential for the use of molasses in a healthier confectionery product development instead of commonly used sugars.
Keywords: Molasses; gelatin; soft candy; rheology; texture; Chemistry; Food Science & Technology